Insight into territorial efficiency of circular economy through data envelopment analysis - Marjanović, Ivana; Stanković, Jelena J.; Östh, John; Marković, Milan; Stanojević, Marina (Frontiers in Environmental Science, 2025)
IntroductionThe circular economy (CE) has emerged as a key paradigm for promoting sustainable economic development by enhancing resource efficiency, minimizing waste, and reducing environmental harm. Despite its widespread adoption in policy frameworks, the practical implementation and efficiency of CE strategies across countries remain insufficiently evaluated.MethodsThis study employs a methodological approach based on Data Envelopment Analysis (DEA) to assess the territorial efficiency of CE implementation across 27 European Union (EU) countries. A composite indicator was constructed using relevant CE metrics obtained from Eurostat, enabling a comparative analysis of national performance in achieving circularity.ResultsThe findings reveal significant variation in CE efficiency among EU countries. The Netherlands, Ireland, and Sweden demonstrate leading performance, while countries such as Bulgaria and Cyprus show considerable room for improvement. Overall, 20 out of 27 EU countries were found to be inefficient in implementing CE practices. A moderate positive correlation was also identified between CE efficiency and the level of countries’ economic development.DiscussionThe results highlight the need for targeted policy interventions to enhance CE performance, particularly in lower-performing countries. The proposed DEA-based framework provides a valuable tool for benchmarking CE efficiency and informing evidence-based policymaking. By identifying leaders and laggards, the study contributes to understanding the territorial dynamics of the circular economy and supports the advancement of more effective and sustainable CE strategies.